Low-cost electronic circuitry for photoacoustic gas sensing - Kanchalar Keeratirawee; Jasmine S. Furter; Peter C. Hauser (My University, 2022)
The circuitry comprises a sine wave generator based on direct digital synthesis, a laser diode driver module, a band-pass frequency filter, a synchronous detector with phase adjustment circuitry and a low pass filter to form an analog lock-in amplifier, and an analog-to-digital converter. A 32-bit ARM microcontroller programmed with the open source Mecrisp dialect of the Forth interpreter language is used to set the frequency, and read the data from the analog-to-digital converter. The circuitry is tethered via a serial interface to a personal computer. A graphical user interface written in Phython allows easy interaction with the microcontroller by sending the appropriate Forth commands. The data acquired is visualized and stored on the personal computer for further processing. The circuitry is easy to build as it is based on through-hole devices, except for two necessary surface mount items, which, however, still can be soldered with a fine tipped soldering iron. The performance of the circuitry was demonstrated by the photoacoustic detection of NO2 using a laser diode with a wavelength of 450 nm.
Keywords: Personal computer; Interface (matter); Lock-in amplifier; SIGNAL (programming language); Sine wave; Spectroscopy and Laser Applications